Development And Service Delivery in Post-Apartheid South Africa: “Quality” Versus “Quantities” of the Pre and Post-Apartheid South Africa - Sebola, Mokoko (Universitas Medan Area, 2023)
This paper intends to determine the contestation between the quality and quantity of service delivery in comparison between pre-apartheid and post-democratic South Africa. There are relative arguments that persist that quality and better service was provided in South Africa during the apartheid government era as compared to the current democratic system era. Contrary to these arguments, post-apartheid South African politicians boast about the service they are providing at the best quality and having closed the segregated service delivery system that was provided and practiced by the apartheid regime. This paper is conceptual, and it uses a desktop methodology to argue and compare the two perspectives in an attempt to find a truthful answer to it. This paper concludes that within the midst of the contestation of such arguments, the current beneficiaries perpetuating such scale of comparison are ignorant of the different contexts of eras of development and challenges and opportunities within which the two regimes operate.